The p75NTR-mediated effect of nerve growth factor in L6C5 myogenic cells - Alessandra de Perini; Ivan Dimauro; Guglielmo Duranti; Cristina Fantini; Neri Mercatelli; Roberta Ceci; Luigi Di Luigi; Stefania Sabatini; Daniela Caporossi (BMC Research Notes, 2017)
Abstract Objective During muscle development or regeneration, myocytes produce nerve growth factor (NGF) as well as its tyrosine-kinase and p75-neurotrophin (p75NTR) receptors. It has been published that the p75NTR receptor could represent a key regulator of NGF-mediated myoprotective effect on satellite cells, but the precise function of NGF/p75 signaling pathway on myogenic cell proliferation, survival and differentiation remains fragmented and controversial. Here, we verified the role of NGF in the growth, survival and differentiation of p75NTR-expressing L6C5 myogenic cells, specifically inquiring for the putative involvement of the nuclear factor κB (NFκB) and the small heat shock proteins (sHSPs) αB-crystallin and Hsp27 in these processes. Results Although NGF was not effective in modulating myogenic cell growth or survival in both standard or stress conditions, we demonstrated for the first time that, under serum deprivation, NGF sustained the activity of some key enzymes involved in energy metabolism. Moreover, we confirmed that NGF promotes myogenic fusion and expression of the structural protein myosin heavy chain while modulating NFκB activation and the content of sHSPs correlated with the differentiation process. We conclude that p75NTR is sufficient to mediate the modulation of L6C5 myogenic differentiation by NGF in term of structural, metabolic and functional changes.